Effect of dietary intake on immune function in athletes - Venkatraman, J. T.; Pendergast, D. R. (Sports Medicine, 2002)
Athletes are exposed to acute and chronic stress that may lead to suppression of the immune system and increased oxidative species generation. In addition, the tendency to consume fewer calories than expended and to avoid fats may further compromise the immune system and antioxidant mechanisms. The exercise stress is proportional to the intensity and duration of the exercise, relative to the maximal capacity of the athlete. Muscle glycogen depletion compromises exercise performance and it also increases the stress. Glycogen stores can be protected by increased fat oxidation (glycogen sparing). The diets of athletes should be balanced so that total caloric intake equals expenditure, and so that the carbohydrates and fats utilised in exercise are replenished. Many athletes do not meet these criteria and have compromised glycogen or fat stores, have deficits in essential fats, and do not take in sufficient micronutrients to support exercise performance, immune competence and antioxidant defence. Either overtraining or under nutrition may lead to an increased risk of infections. Exercise stress leads to a proportional increase in stress hormone levels and concomitant changes in several aspects of immunity, including the following: high cortisol; neutrophilia; lymphopenia; decreases in granulocyte oxidative burst, nasal mucociliary clearance, natural killer cell activity, lymphocyte proliferation, the delayed-type sensitivity response, the production of cytokines in response to mitogens, and nasal and salivary immunoglobulin A levels; blunted major histocompatibility complex II expression in macrophages; and increases in blood granulocyte and monocyte phagocytosis, and pro- and anti-inflammatory cytokines. In addition to providing fuel for exercise, glycolysis, glutaminlysis, fat oxidation and protein degradation participate in metabolism and synthesis of the immune components. Compromising, or overusing, any of these components may lead to immunosuppression. In some cases, supplementation with micronutrients may facilitate the immune system and compensate for deficits in essential nutrients. In summary, athletes should eat adequate calories and nutrients to balance expenditure of all nutrients. Dietary insufficiencies should be compensated for by supplementation with nutrients, with care not to over compensate. By following these rules, and regulating training to avoid overtraining, the immune system can be maintained to minimise the risk of upper respiratory tract infections.